Free triiodothyronine and triglyceride-glucose index interaction on metabolic dysfunction-associated steatotic liver disease risk in euthyroid individuals - Gao, Lei; Cui, Wenxia; Pan, Fenghui; Mu, Dinghuang; Zhou, Weihong; Hu, Yun (Frontiers in Endocrinology, 2025)
BackgroundThe link between thyroid function and insulin resistance and metabolic dysfunction-associated fatty liver disease (MASLD) is becoming increasingly recognized. The primary goal of this study was to investigate the relationship between free triiodothyronine (FT3) levels, the triglyceride-glucose index (TyG) index, and the likelihood of MASLD in euthyroid individuals.MethodsA cross-sectional analysis of 18,298 euthyroid individuals was conducted, comparing 6,144 with MASLD to 12,154 controls. The study evaluated indicators related to clinical, metabolic, and thyroid function. The combined effect of the FT3 and TyG index on the likelihood of MASLD was assessed using logistic regression.ResultsThe MASLD group presented with higher male prevalence, older age, and increased rates of hypertension and diabetes. Significant correlations were observed between FT3, TyG, and metabolic parameters. After controlling for potential confounders, FT3 remained significantly associated with increased MASLD risk (adjusted OR = 1.35, 95% CI: 1.23-1.49; P < 0.001). Similarly, the TyG index was independently associated with higher MASLD risk (adjusted OR = 3.99, 95% CI: 3.40-4.68; P < 0.001). The high FT3 (≥ 4.98 pmol/L)/high TyG (≥ 8.55) group exhibited significantly elevated MASLD risk compared to the low FT3/low TyG group (OR = 5.38, 95% CI: 4.62-6.26; P < 0.001).ConclusionElevated FT3 and TyG index are independently associated with an increased risk of MASLD, and they exhibit a significant synergistic additive interaction.